ZOOM COMO ESTRATEGIA EN EL APRENDIZAJE SIGNIFICATIVO DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES EN INFORMÁTICA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO PERIODO ACADÉMICO OCTUBRE 2023 –MARZO 2024 - ARTEAGA GARAICOA KELVIN PATRICIO (2024)
This research deals with the importance of the use of information and communication technologies in the teaching and learning process, since in contemporary times the use of ICTs within the educational system is essential. For this reason, the present research aims to analyze the importance of the Zoom platform as a meaningful learning strategy in students of the experimental sciences in computer science degree at the Technical University of Babahoyo. The methodology of the study is made up of descriptive, field and exploratory research types; in addition to the inductive method for the particular analysis of each of the findings of the investigative process. The study sample is 205 students and sixteen teachers from the university institution, to whom a survey and interview were applied respectively to obtain the main results on the topic raised. The results allowed us to conclude that: It is increasingly important to integrate information and communication technologies into the educational system, since they represent an innovative pedagogical tool for the development of teaching and meaningful learning processes. The mastery that teachers have regarding the use of the Zoom platform is good, since the majority of students stated that they use appropriate pedagogical strategies to develop an optimal virtual learning environment.